2020
DOI: 10.1007/s00068-020-01501-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome predictors after spinal accessory nerve to suprascapular nerve transfer for restoration of shoulder abduction in traumatic brachial plexus injuries in adults: the effect of time from injury to surgery

Abstract: Background Shoulder abduction is crucial for daily activities, and its restoration is one of the surgical priorities. We evaluated the predictive factors of shoulder abduction functional outcome after spinal accessory nerve (SAN) to suprascapular nerve (SSN) transfer, with special emphasis on the effect of time from injury to the surgery, in the treatment of traumatic brachial plexus injuries. Method This cohort included adult patients who underwent SAN-to-SSN transfer with a preoperative Medical Research Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In addition, there are other factors that contribute to different outcomes of neurogenic shoulder function improvement, such as the interval between injury and surgery ( 18 ), age, and BMI ( 19 ), thus, future studies should examine these factors in greater detail. In our study, we applied PDIC7 transfer to the C5 root in patients aged 16–63 years and the interval between injury and surgery was 1–9 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are other factors that contribute to different outcomes of neurogenic shoulder function improvement, such as the interval between injury and surgery ( 18 ), age, and BMI ( 19 ), thus, future studies should examine these factors in greater detail. In our study, we applied PDIC7 transfer to the C5 root in patients aged 16–63 years and the interval between injury and surgery was 1–9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing nerve root injuries in the context of severe cervical spinal cord injuries resulting in complete paralysis of the extremities has been challenging. Distal-targeted nerve transfers have been successfully performed as a preferred alternative to the site of a proximal injury [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] since the regeneration distance will be much shorter and, therefore, the recovery will be faster. Additionally, in cases of iatrogenic surgical injuries at the proximal cervical spinal level (ACDF), as in the present case report, the distal operative area will have no scarring from previous surgeries, allowing for technical precision in reconstructive efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Fasce et al [ 22 ] reported that patients under age 25 years have better outcomes due to their higher regenerative capability. Solla et al [ 24 ] reported that older patients had worse outcomes. However, our patient was older (45 years) but still achieved all UE functions 17 months after the nerve transfer surgery, as she had external and internal neurolysis of the involved nerve fascicles and release of muscle contractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachial plexus injuries are commonly seen secondary to birth-related trauma or from trauma secondary to a fall, most commonly in a road traffic accident [1][2][3][4]. Injuries involving the upper trunk brachial plexus, i.e., C5, C6, C7 roots, lead to significant disability of shoulder function with loss of shoulder abduction and range of motion.…”
Section: Introductionmentioning
confidence: 99%